Ghost in trouble - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2010)
In her toughest case yet, Bailey Ruth, the irrepressible ghost sleuth, returns to earth to protect Kay Clark, a former Adelaide, Okla., acquaintance, from danger -- and discover who killed Kay's husband.